Building Competitiveness through Cooperation of Enterprises with Banks - Idzik, Marcin (Budowanie konkurencyjności poprzez współpracę przedsiębiorstw z bankami, 2011)
The main line of the analysis consisted of the evaluation of the entrepreneurs’ relationship with the banks. On the basis of the results of the research among the banks’ representatives, we evaluated the magnitude of interest of the banking sector in serving micro-, small and medium-sized enterprises. We also conducted a multifaceted evaluation of the banks as institutions of the external environment of the enterprises. We identified the scope of using the banking products and a highly limited demand for the banking products on the part of the entrepreneurs. The empirical material comprised the results of the newest, unpublished, surveys among the entrepreneurs on a nationwide, representative sample of N = 1400 micro-, small and medium-sized companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 966-978
Keywords: financing enterprises; credits; development barriers; banks; management strategies